2022
DOI: 10.3390/audiolres13010002
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Migraine versus Méniere’s Disease: Diagnostic Utility of Electrocochleography

Abstract: Objectives: The diagnostic criteria for vestibular migraine (VM) and Ménière’s disease (MD) present an important overlap, which leads to a difficult diagnosis in patients presenting with headache, vertigo, hearing loss, ear fullness, and tinnitus. The objective of our study is to determine whether the area-under-the-curve ratio of the summating potentials (SP) and action potentials (AP) curves on electrocochleography (ECoG) helps differentiate VM from MD with or without the use of the well-established clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Our team already demonstrated that around 38% of patients had fulfilled both clinical criteria simultaneously 25 . The association of clinical criteria and ECochG result together can improve the prediction of symptoms improvement with antimigraine treatment in patient presenting with both criteria of MD and MV but has a normal ECochG result 26 . Therefore, these patients will be considered as patients having VM.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our team already demonstrated that around 38% of patients had fulfilled both clinical criteria simultaneously 25 . The association of clinical criteria and ECochG result together can improve the prediction of symptoms improvement with antimigraine treatment in patient presenting with both criteria of MD and MV but has a normal ECochG result 26 . Therefore, these patients will be considered as patients having VM.…”
Section: Discussionmentioning
confidence: 95%
“…25 The association of clinical criteria and ECochG result together can improve the prediction of symptoms improvement with antimigraine treatment in patient presenting with both criteria of MD and MV but has a normal ECochG result. 26 Therefore, these patients will be considered as patients having VM. Observable inner ear hydrops on MRI imaging with intratympanic or intravenous injection of gadolinium compelled a series of new MRI inner ear researchers in the possibility that an identifiable diagnosis of hydrops on MRI would serve as the gold standard for MD diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…We appreciate the comments made by Hornibrook (2024) [ 1 ] on our paper reporting on the Vestibular Migraine (VM) versus Ménière’s Disease (MD): Diagnostic Utility of Electrocochleography (ECochG) [ 2 ].…”
mentioning
confidence: 99%
“…Hornibrook unaware of this information, assumed in his comment that audiologists have not employed the tone burst stimulus ECochG because it requires specialty co-operation and customized equipment that cannot be achieved by the standard commercial systems used by audiologists. However we realized throughout the period where we included the TT-TBS in our protocol that these data of TT-TBS were not as helpful as Hornibrook reported; that’s why we didn’t included their analysis in our published article to report utility of ECochG in VM and MD [ 2 ].…”
mentioning
confidence: 99%
“…I wish to comment on an aspect of the recently published article by Saliba I. et al, titled Vestibular Migraine versus Meniere’s Disease: Diagnostic Utility of Electrocochleograpy [ 1 ]. It is commendable that the authors would use the EcochG to make a distinction, even though the technique is becoming unfashionable with the increased use of MRI inner-ear imaging.…”
mentioning
confidence: 99%